2015
DOI: 10.1186/s13063-015-1036-z
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic effect of short-term arginyl-fructose supplementation in subjects with prediabetes and newly diagnosed type 2 diabetes: randomized, double-blinded, placebo-controlled trial

Abstract: BackgroundA previous study reported that arginyl-fructose may have great value as a functional food with antioxidant and antidiabetic activities. However, there have been few clinical studies on the efficacy of arginyl-fructose supplementation for blood glucose control.MethodsIn this double-blind, placebo-controlled study, 60 Korean subjects with prediabetes or type 2 diabetes mellitus were randomly assigned to placebo or test groups. The test group subjects received 1500 mg/day arginyl-fructose. Fasting serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…In our previous study, we reported that arginyl-fructose (AF) and arginyl-fructosyl-glucose (AFG) produced by heat-processing in Korean ginseng can reduce carbohydrate absorption by inhibiting intestinal carbohydrate hydrolyzing enzymes in both in vitro and in vivo animal models [ 16 , 17 ]. The postprandial anti-hyperglycemia effect of AF from heat-processed Korean ginseng in db/db animal model and human clinical trials was also reported by our previous study [ 18 , 19 ].…”
Section: Introductionsupporting
confidence: 80%
“…In our previous study, we reported that arginyl-fructose (AF) and arginyl-fructosyl-glucose (AFG) produced by heat-processing in Korean ginseng can reduce carbohydrate absorption by inhibiting intestinal carbohydrate hydrolyzing enzymes in both in vitro and in vivo animal models [ 16 , 17 ]. The postprandial anti-hyperglycemia effect of AF from heat-processed Korean ginseng in db/db animal model and human clinical trials was also reported by our previous study [ 18 , 19 ].…”
Section: Introductionsupporting
confidence: 80%
“…This study has shown that TNF-α and IL-1β in the serum of mice significantly increase, and immunofluorescence analysis also indicated that AFG could antagonize NF-κB overexpression and play an important role in cisplatin-induced intestinal toxicity. Meanwhile, the specific expression of NF-κB plays a harmful role in the expression of colitis-related proteins causing intestinal injury, 45 and inflammatory cells also lead to the emergence and development of a variety of diseases, including cisplatin-induced renal and gastrointestinal injury. 46 Consistently, this study has indicated the activation of NF-κB and the enhanced expression of pro-inflammatory proteins such as IKKα/β and IκBα.…”
Section: Discussionmentioning
confidence: 99%
“…Arginyl-fructose has potential as a pharmacological agent for glycemic control since it significantly reduces postprandial blood glucose levels in rodents and humans. In contrast, glucose-related biomarkers including HbA1, insulin, and C-peptide levels were not significantly improved by dietary supplementation with arginyl-fructose [ 153 , 154 ].…”
Section: Effects Of Nutrients On Gene Expression In the Pathogenesmentioning
confidence: 99%